Leukocytosis, monocytosis, and eosinophilia in systemic mastocytosis: analysis of phenotype, genetics and prognosis in 596 patients from the GREM registry - Lübke, Johannes; Naumann, Nicole; Dangelo, Vito; Fabarius, Alice; Metzgeroth, Georgia; Horny, Hans-Peter; Sotlar, Karl; Hofmann, Wolf-Karsten; Rudelius, Martina; Schwaab, Juliana; Reiter, Andreas (The journal of allergy and clinical immunology. In practice, 2026)
Background - Leukocytosis, monocytosis, and eosinophilia (L/M/E) are recurrent findings in systemic mastocytosis (SM). - Objective - To investigate the prevalence of L/M/E in SM and assess their association with clinical phenotype, mutational profile, and overall survival (OS) in advanced SM (AdvSM). - Methods - Within the German Registry on Disorders of Eosinophilia and Mast Cells, 596 patients with SM (91% KIT D816V positive; 270 AdvSM, 326 non-AdvSM) were analyzed for L/M/E. - Results - In comparison with non-AdvSM, patients with AdvSM had significantly higher leukocyte (median 9.4 vs 6.9 × 109/L), monocyte (median 0.7 vs 0.5 × 109/L), and eosinophil counts (median 0.3 vs 0.1 × 109/L; all P < .001), with the highest counts (leukocytes: 10.2 × 109/L, monocytes: 0.9 × 109/L, and eosinophils: 0.3 × 109/L; all P < .001) being observed in SM with associated hematologic neoplasm (SM-AHN). High counts of L/M/E correlated with an increased number of additional somatic mutations (P = .012, P < .001, and P = .020), with monocytosis being specially associated with mutations in ASXL1 (odds ratio [OR]: 2.91; 95% confidence interval [CI]: 1.5-5.8), SRSF2 (OR: 2.2; 95% CI: 1.2-4.0), and TET2 (OR: 2.2; 95% CI: 1.2-4.0). In AdvSM, optimal OS cutoff values based on maximally selected rank statistics were ≥16.8 × 109/L for leukocytosis (median OS: 1.6 vs 4.7 years, P < .001), ≥1.1 × 109/L for monocytosis (2.9 vs 4.8 years, P < .001), and ≥1.5 × 109/L for eosinophilia (1.7 vs 5.0 years, P < .001). Monocytosis and/or eosinophilia defined a 3-tiered risk model (median OS: 1.60 vs 3.04 vs 6.94 years, P < .001). - Conclusions - Elevated counts of L/M/E are indicative of AdvSM and within AdvSM associated with additional somatic mutations, a subtype of SM-AHN and poor prognosis.
Online veröffentlicht: 24. September 2025, Artikelversion: 7 January 2026
Gesehen am 03.02.2026